Exploring the Role of Netflix Cartoon Movies in Enhancing Students’ Vocabulary Mastery - Rimayanti Rimayanti; Yugi Diraga Prawiyata; Rini Fadhillah Putri; Nurhafni Siregar (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to explore the role of Netflix cartoon movies in enhancing elementary school students' English vocabulary mastery. This research employed a qualitative descriptive approach involving 5 fourth-grade students at SDN 107420 Desa Tengah, Deli Serdang Regency. Data were collected through three instruments: vocabulary tasks, questionnaires, and semi-structured interviews. Data analysis used the interactive model by Miles, Huberman, and Saldana through the stages of data condensation, data display, and conclusion drawing. The findings revealed that Netflix cartoon movies positively contributed to students' vocabulary mastery, as evidenced by improved participation, comprehension, and ability to use vocabulary in simple contexts. Students responded positively to this medium, stating that learning became more enjoyable, interesting, and less boring compared to conventional memorization methods. These findings are supported by Krashen's Input Hypothesis and Mayer's Multimedia Learning Theory, which explain that the combination of visual and auditory input in Netflix cartoon movies creates meaningful learning experiences for young learners. This study recommends the integration of Netflix cartoon movies as an innovative medium for vocabulary learning at the elementary school level.